Conjugate Addition of Pyrazoles to Halogenated Nitroso- and Azoalkenes: A New Entry to Novel Bis(pyrazol-1-yl)methanes - Grosso, Carla; Lemos, Américo; Pinho e Melo, Teresa M. V. D. (Synlett, 2014)
A new and versatile synthetic approach towards bis(pyrazolyl)methanes, based on 1,4-addition of pyrazoles to conjugated α-halogenated nitroso- and azoalkenes, is described. Tris(pyrazolyl)methanes can also be obtained by this methodology.
Keywords: bis(pyrazolyl)methanes; conjugate addition; α-halogenated nitrosoalkenes; α-halogenated azoalkenes; tris(pyrazolyl)methanes